Description of Protosticta jirapornae sp. nov. from northern Thailand (Odonata: Platystictidae) - Makbun, Noppadon (Zootaxa, 2025)
Protosticta jirapornae sp. nov. is described and illustrated based on specimens of both sexes collected from Chiang Mai Province, Thailand. This taxon was previously recognised as the northern population of P. khaosoidaoensis Asahina, 1984, which is geographically isolated from its type locality in Chanthaburi Province, eastern Thailand. The new species can be distinguished from P. khaosoidaoensis and other closely related congeners by the distinctive markings on the prothorax and synthorax in both sexes, as well as the structure of the male anal appendages and the morphology of the genital ligula.